The limits to freedom to contract: Supreme court case summary: Leiman, Ricardo v Noble Resources Ltd - TAN, Jia Xin (Institutional Knowledge at Singapore Management University, 2021)
In line with the principle of freedom to contract, the courts will give effect to the intention of the parties in creating their contract, and also hold them to their duty to perform their primary obligations under such contract. However, where the contracting parties agree to vest certain decision-making powers to a specific (non-judicial) entity, to what extent may a court review the exercise of powers by such entity?